Microdomain calcium fluctuations as a colored noise process - Wegner, Frederic von; Wieder, Nicolas Wolfgang; Fink, Rainer (Frontiers in genetics, 2014)
Calcium ions play a key role in subcellular signaling as localized transients of the intracellular calcium concentration modify the activity of ion channels, enzymes and transcription factors, among others. The intracellular calcium concentration is inherently noisy, as diffusion, the transient binding to and dissociation from buffer molecules and stochastically gating calcium channels contribute to the fluctuations of the local copy number of Ca2+ ions. We study the properties of the fluctuating calcium concentration in sub-femtoliter volumes using an exact stochastic simulation algorithm and approximations to the exact stochastic solution.
Gesehen am 14.10.2020